SARS-COV-2 Neutralizing IgG Antibodies in Patients Recovered from COVID-19 in a Hospital-Based Study: From Predictions to Reality - Hamzullah Khan , Fazli Bari , Tahir Mohammad ,Rizwanullah Jan (Journal of Rawalpindi Medical College, 2021)
Background: The duration and immunity nature in form of antibodies to COVID-19 is still not clear. But so far we know that an immune response protects the individuals from future illness for some specific time. The presence or absence of immunity tells us about the future transmission of illness. Objectives: To determine the frequency of antibodies to COVID-19 after three weeks of negative PCR report. To predict the association of the antibodies values with severity of the disease the patient had in recent past. Material and methods: We did a cross sectional study in department of Pathology on 36 patients recovered from COVID-19 from 3rd July 2020 to 31st July 2020. Antibodies level was measured by electro-chemiluminescence immunoassay using Roche Cobas E411 Chemistry Analyzer for which commercial kits of Roche diagnostics were used as per the instructions of the manufacturer, in respondents after 3 weeks of a negative PCR report. Results: The mean with standard deviation for numerical variables i.e. (age and antibodies) was 34+11 years and 34.52+12.71 respectively. 29(80.55%) were males and 7(19.45%) females. The mean antibodies level was statically significantly higher in patients with age less than 50 years (p-value: 0.01). Patients who had severe symptoms at time of being reported positive by PCR had significantly higher antibodies cut off values as compared to asymptomatic positive patients (p-value:0.04). Clinically sever Covid-19 patients positively moderates with an increase in the values of the post infection anti SARS-COV-2 antibodies supported by an interaction term with (β=0.388**; ΔR²=0.126, p-value=0.02). Male gender supported by the results of an interaction term with (β=0.388**; ΔR²=0.126, p-value=0.02) had sever disease as compared to female. Conclusion: The higher anti SARS-COV-2 antibodies were reported in patients with age <50 years and in patients who had severe symptoms or history of hospitalization during the infectious period. There was a statistically significant relationship supported by the interactions terms of higher post infection antibodies level with male gender, an increase in age and with history of sever disease or hospitalization.